Influence of the fabrication process of copper matrix composites on cavitation erosion resistance - Ružić, Jovana; Stašić, Jelena; Božić, Dušan; Dojčinović, Marina; Volkov-Husović, Tatjana (Metallurgical and Materials Engineering, 2018)
Copper matrix composites reinforced with ZrB2 particles were produced in two ways: by hot pressing (HP) and laser-sintering process. Powder mixture Cu-Zr-B was mechanically alloyed before densification processes. Variations in the microstructure of treated samples obtained during cavitation test were analyzed by scanning electron microscopy (SEM). Cavitation erosion resistance was investigated with the standard test method for cavitation erosion using vibratory apparatus. Changes in mechanical alloying duration show a strong influence on cavitation erosion resistance of Cu-ZrB2 composites regardless the number of reinforcements. Laser-sintered samples show better cavitation erosion resistance than hot-pressed samples.